187k views
4 votes
Please do 41 and 46. Please show your work and explain how you did it. Thank you!

Please do 41 and 46. Please show your work and explain how you did it. Thank you!-example-1
User Terrence M
by
6.3k points

2 Answers

5 votes

\bf 41)\\\\ 8x^4-24x^3+18x^2\implies 2x^2(\stackrel{2,2}{4}x^2\stackrel{(2\cdot -3)+(2\cdot -3)}{-12}x+\stackrel{3,3}{9}) \\\\\\ 2x^2(2x-3)(2x-3)\\\\ -------------------------------\\\\ 46)\\\\ x^2(x-1)-25(x-1)\implies \stackrel{\stackrel{common}{factor}}{(x-1)}(x^2-25) \\\\\\ (x-1)\stackrel{\textit{difference of squares}}{(x^2-5^2)}\implies (x-1)(x-5)(x+5)
User Hasani
by
7.0k points
2 votes

8x^4-24x^3+18x^2=2x^2(4x^2-12x+9)=2x^2(4x^2-6x-6x+9)\\\\=2x^2[2x(2x-3)-3(2x-3)]=2x^2(2x-3)(2x-3)


x^2(x-1)-25(x-1)=(x-1)(x^2-25)\\\\=(x-1)(x^2-5^2)=(x-1)(x-5)(x+5)\\\\Used:\ a^2-b^2=(a-b)(a+b)
User Dachstein
by
6.5k points